2011
DOI: 10.5301/hip.2011.6498
|View full text |Cite
|
Sign up to set email alerts
|

Hip Resurfacing Arthroplasty in Patients with Varus Deformity of the Femoral Neck-Shaft Angle

Abstract: Hip resurfacing arthroplasty (HRA) in patients with a varus deformity of the femoral neck-shaft angle (NSA) is associated with poorer outcomes. Our experience has not reflected this. We examined the Oxford Hip Scores (OHS), Harris Hip Scores (HHS) and outcomes of patients with varus hips against a normal cohort to ascertain any significant difference. We identified 179 patients. Measurement of the femoral neck-shaft angle was undertaken from antero-posterior radiographs pre-operatively. The mean NSA was 128.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A neck‐shaft angle greater than 140° tends to result in valgus of the knee joint ipsilaterally in the lower extremity into which the prosthesis is implanted (Rozkydal and Janicek, ). Varus deformity occurs in patients with a neck‐shaft angle of less than 122° (Carlile et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A neck‐shaft angle greater than 140° tends to result in valgus of the knee joint ipsilaterally in the lower extremity into which the prosthesis is implanted (Rozkydal and Janicek, ). Varus deformity occurs in patients with a neck‐shaft angle of less than 122° (Carlile et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the rate of each complication was relatively low, a composite complication (implant failure) was defined as the primary outcome. Hip varus deformity was defined as the femoral neck shaft angle <120 • (19). A fracture that had not healed for more than 8 months or had abnormal activity at the broken end was defined as nonunion (20).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of osteoarthritis secondary to coxa vara, which is associated with low NSA, overgrowth of the GT and limp, causing pelvic obliquity and degeneration of the lumbar spine, is challenging for surgeons. 3 , 8 , 11 Many methods have been proposed for the restoration of normal anatomic structure and improvement of biomechanics, 2 , 3 , 6 , 10 , 27 while little attention has been given to modular THA. We demonstrated that the outcomes of modular THA in patients with coxa vara who were followed up for more than 5 years were inspiring and positive, which achieved the expected satisfaction for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, THA performed after failed trochanteric osteotomies, including trochantoplasty, is also known to be of increased operating time and blood loss, more technical difficulties and higher complication rates (6%-31%). 30–33 Osawa et al 32 reported that the HHS after THA at the final follow-up was significantly poorer in the osteotomy group than in the primary group due to poor physical function caused by osteotomy, and Carlile et al 27 suggested there were higher restrictions on patient selection and the surgical techniques for resurfacing arthroplasty in coxa vara. More complicated arthritic hips, such as hips with large cysts, osteopenia, LLD >1 cm or a diminished FO, that usually occurs in coxa vara, may be better served by a modular THA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation